Battery diaphragm as well as preparation method and application thereof
By using inorganic particles, acrylate adhesives and esterified nanocellulose fibers in the coating layer of the lithium battery separator, the ester-based content is controlled, and the problems of insufficient heat resistance and excessive moisture content of the separator at high temperatures are solved, thereby achieving higher safety and electrical properties.
Patent Information
- Application Number
- CN202411954540.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
AI Technical Summary
The existing lithium battery separators are insufficient in heat resistance at high temperatures, which can easily lead to short-circuit explosion of lithium batteries. At the same time, the use of cellulose leads to excessive moisture content of the separator, affecting safety.
The coating layer containing inorganic particles, acrylate adhesives and esterified nanocellulose fibers was used to control the content of the ester group in each square meter of coating layer to improve the heat resistance and wettability of the separator.
It realizes excellent heat resistance and high wettability of the battery separator, effectively improving the safety and electrical performance of the battery.
Smart Images

Figure BDA0005215554790000201
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of diaphragms, and in particular relates to a battery diaphragm and a preparation method and application thereof. Background Art
[0002] With the development of lithium batteries, separators, as an important component of batteries, have higher requirements on the safety and energy density of lithium batteries.
[0003] At present, the most commonly used coating materials for coating diaphragms include ceramics, but the heat resistance of ceramic coatings is insufficient and they are prone to shrinkage at high temperatures, which can easily cause short circuits and explosions in lithium batteries. The existing solution is to add cellulose and ceramics as coating materials. Since cellulose itself is resistant to high-temperature decomposition, the heat resistance of the coated diaphragm can be improved. However, due to the presence of a large number of hydroxyl groups on the surface of cellulose, while improving the heat resistance of the diaphragm, it will also cause the moisture content in the diaphragm to be too high, which will lead to poor safety of lithium batteries. At the same time, the presence of a large number of hydroxyl groups also causes the intermolecular forces of the slurry to be too strong, which is manifested as high viscosity, easy agglomeration, and poor processing performance.
[0004] Therefore, how to solve the agglomeration problem caused by the strong intermolecular forces while maintaining the performance advantages of cellulose itself, and then develop a battery separator that can take into account both heat resistance and wettability, is still a technical problem that needs to be urgently solved in this field. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a battery separator and a preparation method and application thereof. The battery separator has excellent heat resistance and high wettability, and can be applied to batteries to effectively improve the safety and electrical performance of the batteries.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a battery separator, comprising a substrate and a coating layer disposed on one or both sides of the substrate;
[0008] The coating layer comprises inorganic particles, acrylic adhesive and esterified nanocellulose fibers;
[0009] The content of ester groups in the coating layer per square meter is 0.5wt% to 4wt%, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt% or a range consisting of any two of them.
[0010] First, since the coating layer of the battery separator provided by the present invention contains esterified nanocellulose fibers, the esterified nanocellulose fibers are obtained by partially replacing a large number of hydroxyl groups contained in the nanocellulose with ester groups. On the one hand, after a large number of hydroxyl groups in the nanocellulose are replaced with ester groups, the intermolecular forces of the slurry after dispersion can be reduced, thereby avoiding the problems of poor processing performance and rapid agglomeration caused by excessive viscosity of the slurry; on the other hand, the degree of ester group generation (the amount of hydroxyl groups replaced) can be controlled to reduce the moisture content of the battery separator while ensuring that the obtained battery separator has high wettability and ion pass rate, thereby effectively improving the safety of the battery; in addition, the addition of the esterified nanocellulose fibers also effectively improves the heat resistance of the obtained battery separator (the thermal decomposition temperature of conventional nanocellulose is about 360°C, while the thermal decomposition temperature of the esterified nanocellulose fibers is close to 400°C);
[0011] Secondly, the content of ester groups in the coating layer per square meter is limited to 0.5wt% to 4wt%. On the one hand, if the content of ester groups in the coating layer per square meter is lower than 0.5wt%, it is easy to cause the viscosity of the slurry to be still too high, the processing performance is poor, and the wettability of the resulting battery separator is reduced; on the other hand, if the content of ester groups in the coating layer per square meter is higher than 4wt%, it is easy to cause too many polar groups in the coating layer, and the oxidation reaction of the coating layer at the battery electrode end is too strong, resulting in a potential difference between the positive and negative electrode ends of the battery, causing failure and a series of problems such as bulging.
[0012] In the present invention, the above-mentioned "content of ester groups in the coating layer per square meter" refers to the amount of ester groups contained in the coating layer per square meter in the single-sided coating, and the "ester groups" therein include the sum of the ester groups from the esterified nanocellulose fibers and the ester groups from the acrylic adhesive, which can be specifically obtained by testing as follows:
[0013] First, a series of standard samples with different ester group contents need to be prepared and the infrared light tester is used to measure the standard samples at 1750cm -1 ~1735cm -1 The area of the strong absorption peak at 1750cm is obtained by data collection and processing, and then the standard curve model is obtained. Then, an infrared light tester is used to measure the sample to be tested at 1750cm -1 ~1735cm -1 The area of the strong absorption peak at is calculated, and finally the content of ester groups in the sample to be tested is calculated according to the standard curve model.
[0014] In some preferred embodiments, the content of ester groups in the coating layer per square meter is 1wt% to 3wt%, for example, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt% or a range consisting of any two of them.
[0015] In the present invention, there is no special restriction on the thickness of the coating layer, and it can be set with reference to the thickness of conventional coating layers in the art. However, in order to ensure that the obtained battery separator has the most excellent electrolyte wettability and heat resistance, and is thinner and lighter, the thickness of the coating layer is preferably 0.5μm to 5μm, for example, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or a range consisting of any two of them.
[0016] In some preferred embodiments, the average diameter of the esterified nanocellulose fibers is 100 nm to 500 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm or a range consisting of any two thereof.
[0017] In some preferred embodiments, the D 50 The particle size is 0.1 μm to 1 μm, for example, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm or a range consisting of any two thereof.
[0018] In the present invention, the D of the inorganic particles is defined as 50 The particle size being within the above range can ensure that the inorganic particles are evenly distributed in the holes of the overlapping grid structure formed by the esterified nanocellulose fibers, thereby giving the coating layer a higher structural strength.
[0019] In the present invention, there is no particular restriction on the specific type of the inorganic particles, and any ceramic material that can be used for the coating layer material in the art can be selected. However, in order to optimize the heat resistance and conductivity of the resulting battery separator, the inorganic particles preferably include any one of boehmite, alumina or silica, or a combination of at least two of them.
[0020] In some preferred embodiments, the coating layer also includes lithiated nanofiber microspheres. The addition of the lithiated nanofiber microspheres can effectively avoid the problem of large differences in mechanical strength in various directions and large differences in thermal shrinkage of the resulting battery separator caused by the addition of esterified nanocellulose fibers. Its addition can effectively improve the mechanical properties of the resulting battery separator.
[0021] In some preferred embodiments, the content of lithium ions in the coating layer per square meter is an ester group content of 5 to 15%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any two thereof, and more preferably 7 to 10%.
[0022] In the present invention, the content of lithium ions and the content of ester groups in the coating layer per square meter are further limited to satisfy the above relationship, which can ensure that the passage rate of lithium ions in the electrolyte is appropriate, thereby preventing the deposition and crystallization of lithium ions caused by excessive difference in lithium ion concentration at both ends of the battery separator, thereby affecting the safety of the battery.
[0023] In the present invention, the "lithium ion content in the coating layer per square meter" also refers to the amount of lithium ions contained in the coating layer per square meter in the single-sided coating layer, and the "lithium ions" therein all come from the lithiated nanofiber microspheres, which can be specifically obtained by ICP-OES spectroscopy testing in accordance with GB / T 30903-2014.
[0024] In some preferred embodiments, the inorganic particles have a D 50 Particle size and D of lithiated nanofiber microspheres 50 The particle size ratio is (2-200):1, for example, 2:1, 5:1, 10:1, 20:1, 40:1, 60:1, 80:1, 100:1, 120:1, 140:1, 160:1, 180:1, 200:1 or a range consisting of any two thereof; the D of the inorganic particles is limited 50 Particle size and D of lithiated nanofiber microspheres 50 If the particle size ratio is within the above specific range, the D 50 If the particle size is too small, it will be too dispersed at the micro level and cannot achieve the effect of strengthening the mechanical strength. 50 When the particle size is too large, it will easily block the porous structure formed by the fibers, and because it is a three-dimensional structure with a relatively large specific surface area, it will also increase the moisture content in the resulting battery separator.
[0025] In some preferred embodiments, the mass ratio of the total mass of the esterified nanocellulose fibers and the lithiated nanofiber microspheres to the inorganic particles is (0.1-0.4):1, for example, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1 or a range consisting of any two of them, more preferably (0.05-0.3):1; limiting the mass ratio of the total mass of the esterified nanocellulose fibers and the lithiated nanofiber microspheres to the inorganic particles within the above range can make the obtained electrode The cell diaphragm can better balance the moisture content and wettability; if the ratio of the total mass of the esterified nano-cellulose fibers and the lithiated nano-fiber microspheres to the mass of the inorganic particles is relatively too low, it is easy to cause the coating layer to be relatively thin and unable to reach the designed thermal shrinkage temperature, and unable to meet higher wettability requirements; if the ratio of the total mass of the esterified nano-cellulose fibers and the lithiated nano-fiber microspheres to the mass of the inorganic particles is too high, it is easy to cause the moisture content in the coating layer to be too high, and the requirements for the production process are too high, and the battery is prone to failure.
[0026] In some preferred embodiments, the mass ratio of the acrylic adhesive to the inorganic particles is (0.02-1):1, for example 0.02:1, 0.04:1, 0.06:1, 0.08:1, 0.1:1, 0.2:1, 0.4:1, 0.6:1, 0.8:1, 1:1 or a range consisting of any two of them, and further preferably (0.03-0.06):1.
[0027] In the present invention, there is no special requirement for the type of the acrylic adhesive. The acrylic adhesive commonly used in the art can be selected, including but not limited to homopolymers of acrylic acid, acrylic esters or acrylic salts, or copolymers of any one or more of the above monomers, or a mixture of homopolymers and copolymers containing any one or more of the above monomers.
[0028] In some preferred embodiments, the mass ratio of the esterified nanocellulose fibers to the lithiated nanofiber microspheres is 1:(0.1-0.5), for example, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5 or a range consisting of any two of them, and more preferably 1:(0.2-0.3).
[0029] In the present invention, there are no special requirements for the thickness and type of the substrate. The thickness can be set according to the conventional thickness in the art and the substrate commonly used in the art can be selected. However, in order to ensure that the obtained battery separator has the best air permeability, electrolyte wettability and heat resistance, and is thinner and lighter, the thickness and type of the substrate are preferably limited as follows:
[0030] In some preferred embodiments, the thickness of the substrate is 4 μm to 12 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or a range consisting of any two thereof.
[0031] In some preferred embodiments, the substrate comprises a polyolefin substrate.
[0032] In some more preferred embodiments, the material of the polyolefin substrate includes any one or a combination of at least two of homopolymers or copolymers of ethylene, propylene, 1-butene, pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, and 1-decene.
[0033] In a second aspect, the present invention provides a method for preparing a battery separator, the method comprising: coating a slurry on one or both sides of a substrate, and drying the slurry to obtain the battery separator;
[0034] The slurry is obtained by uniformly mixing inorganic particles, acrylic adhesive, esterified nanocellulose fibers and optionally lithiated nanofiber microspheres in water.
[0035] In the present invention, there is no special limitation on the coating method, rate and temperature. A conventional coating method in the art can be selected, and coating can be performed at a conventional coating rate and temperature. However, in order to achieve the best coating effect and the highest coating efficiency, the coating method, rate and temperature are preferably selected as follows in combination with the viscosity range of the slurry:
[0036] In some preferred embodiments, the coating method is roller coating.
[0037] In some preferred embodiments, the coating rate is 80 m / min to 130 m / min, for example, 80 m / min, 90 m / min, 100 m / min, 110 m / min, 120 m / min, 130 m / min or a range consisting of any two of them; if the coating rate is too fast, problems such as missing coating and uneven surface density will occur, and if the coating rate is too slow, the coating efficiency will be affected.
[0038] In some preferred embodiments, the coating temperature is 60°C to 70°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C or a range consisting of any two of them; if the coating temperature is too high, the edges of the resulting coated diaphragm will warp to varying degrees, and if the coating temperature is too low, it will easily lead to the surface of the resulting coating film not being dried.
[0039] In some preferred embodiments, the viscosity of the slurry is 10 cp to 100 cp, for example, 10 cp, 20 cp, 40 cp, 60 cp, 80 cp, 100 cp or a range consisting of any two of them; the test conditions for the above viscosity are 100 rpm and 25°C.
[0040] In some preferred embodiments, the content of inorganic particles in the slurry is 15 wt% to 25 wt%, for example, 15 wt%, 17 wt%, 19 wt%, 21 wt%, 23 wt%, 25 wt% or any two thereof.
[0041] In some preferred embodiments, the content of the acrylic adhesive in the slurry is 0.1wt% to 1wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or a range consisting of any two of them.
[0042] In some preferred embodiments, the content of esterified nanocellulose fibers in the slurry is 1 wt% to 5 wt%, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt% or any two thereof.
[0043] In some preferred embodiments, the content of lithiated nanofiber microspheres in the slurry is 0.5wt% to 1.5wt%, for example, 0.5wt%, 0.7wt%, 0.9wt%, 1.1wt%, 1.3wt%, 1.5wt% or any two thereof.
[0044] In some preferred embodiments, the method for preparing the slurry comprises the following steps:
[0045] Mixing inorganic particles and carboxylic acid dispersant A in water to obtain an inorganic particle premix solution;
[0046] The nanofiber microspheres are subjected to a lithiation treatment to obtain lithiated nanofiber microspheres;
[0047] The cellulose fibers and the carboxylic acid dispersant B are mixed in water to obtain a cellulose fiber premix, the obtained cellulose fiber premix is placed in an ultrasonic cavitation machine for circulation treatment, filtered and dried to obtain esterified microcrystalline cellulose fibers, the obtained esterified microcrystalline cellulose fibers are added to dimethylacetamide for stirring, and then tetrabutylammonium hydroxide is added for reaction, washed, filtered and dialyzed to obtain a suspension, and the obtained suspension is dried to obtain esterified nanocellulose fibers;
[0048] The inorganic particle premix, esterified nanocellulose fibers and lithiated nanofiber microspheres are dispersed in water, placed in an ultrasonic cavitation machine for cavitation treatment, and an acrylic ester adhesive is added for dispersion to obtain the slurry.
[0049] In the slurry preparation method provided by the present invention, inorganic particles are dispersed in water using a carboxylic acid dispersant A, which generates a large amount of hydrogen ions during the hydrolysis process and can serve as a dispersant for the inorganic particles, thereby helping to obtain a uniformly dispersed inorganic particle premix (with a concentration of about 20%), and can also serve as a prerequisite product for cellulose functional group replacement; at the same time, an ultrasonic cavitation machine is introduced to circulate the cellulose premix consisting of cellulose fibers and the carboxylic acid dispersant B. Due to the presence of ultrasonic cavitation, high temperature and high pressure are generated, accompanied by micro-jet. During the ultrasonic process, the high temperature and high pressure weaken the intermolecular force of the cellulose fibers, destroy the hydrogen bonds between the molecules, and Destroying the hydrogen bonds between cellulose fibers while retaining the overall crystalline structure is helpful to form esterified microcrystalline cellulose fibers, and then the obtained esterified microcrystalline cellulose fibers are limitedly dissolved by a mixed solution of dimethylacetamide solution and tetrabutylammonium hydroxide to obtain esterified nanocellulose fibers; in addition, the inorganic particle premix, esterified nanocellulose fibers and lithiated nanofiber microspheres are cavitated in water. During the cavitation process, the inorganic particle aggregates are destroyed by the microjets, and the micron-sized inorganic particles produced by agglomeration are broken into nano-sized particles by the microjets formed by the cavitation effect, which are more evenly dispersed in the dispersion system, thereby obtaining a slurry with more even dispersion and relatively low viscosity.
[0050] In some preferred embodiments, the carboxylic acid dispersant A and the carboxylic acid dispersant B each independently include any one of citric acid, malic acid, tartaric acid or oxalic acid, or a combination of at least two thereof.
[0051] In some preferred embodiments, the mass ratio of the carboxylic acid dispersant A to the inorganic particles is 1:(16-24), for example, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24 or a range consisting of any two of them.
[0052] In some preferred embodiments, the mixing of the inorganic particles and the carboxylic acid dispersant A is performed under stirring.
[0053] In some more preferred embodiments, the stirring speed is 1500-2000 rpm, for example, 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm or a range consisting of any two of them.
[0054] In some more preferred embodiments, the stirring temperature is 20-50°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C or a range consisting of any two thereof.
[0055] In some more preferred embodiments, the stirring time is 1 to 2 h, for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h or a range consisting of any two thereof.
[0056] In some preferred embodiments, the mass ratio of the carboxylic acid dispersant B to the cellulose fiber is (0.1-1):(10-50), for example, 0.1:10, 0.2:15, 0.3:20, 0.4:30, 0.5:35, 0.6:40, 0.8:45 or a range consisting of any two of them.
[0057] In the present invention, there is no special limitation on the method of the lithiation treatment, and the fiber microspheres can be lithiation treated with an existing lithiation reagent. Exemplarily, the lithiation reagent includes lithium hydroxide.
[0058] In some preferred embodiments, the method of placing the obtained cellulose premix in an ultrasonic cavitation machine for circulation treatment comprises: placing the cellulose fiber premix in an ultrasonic cavitation machine, at a frequency of 20kHZ to 40kHZ (e.g., 20kHZ, 22kHZ, 24kHZ, 26kHZ, 28kHZ, 30kHZ, 32kHZ, 34kHZ, 36kHZ, 38kHZ, 40kHZ or any two thereof) and 0.2m 3 / hr~2m 3 / hr (e.g. 0.2m 3 / hr, 0.4m 3 / hr, 0.6m 3 / hr, 0.8m 3 / hr、1m 3 / hr、1.2m 3 / hr、1.4m 3 / hr、1.6m 3 / hr、1.8m 3 / hr、2m 3 / hr or a range consisting of any two of them) for 20min to 40min (for example, 20min, 22min, 24min, 26min, 28min, 30min, 32min, 34min, 36min, 38min, 40min or a range consisting of any two of them); the cellulose fiber premix is added into the ultrasonic cavitation machine, and specific control frequency, flow rate and treatment time are adopted. The coordination of the three can ensure the dispersion effect while taking into account the economic efficiency of production; if it exceeds the range specified in this scheme, the cavitation effect will be reduced to varying degrees, the dispersion time will be prolonged or the energy consumption will be increased, and the overall dispersion will be incomplete.
[0059] In some preferred embodiments, the temperature of the cavitation treatment in the ultrasonic cavitation machine is 25°C to 60°C (for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or a range consisting of any two thereof), the time is 0.3h to 0.8h (for example, 0.3h, 0.4h, 0.5h, 0.6h, 0.7h, 0.8h or a range consisting of any two thereof), and the frequency is 20kHz to 30kHz (for example, 20kHz, 21kHz, 22kHz, 23kHz, 24kHz, 25kHz, 26kHz, 27kHz, 28kHz, 29kHz, 30kHz) or a range consisting of any two thereof.
[0060] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises at least one of the battery separators described in the first aspect or the battery separators prepared by the preparation method described in the second aspect.
[0061] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] The battery separator provided by the present invention comprises a substrate and a coating layer arranged on one or both sides of the substrate, wherein the coating layer contains inorganic particles, an acrylic adhesive and esterified nanocellulose fibers, and the content of ester groups in the coating layer per square meter is 0.5wt% to 4wt%; by introducing esterified nanocellulose fibers and inorganic particles into the coating layer for matching, and limiting the content of ester groups in the coating layer per square meter to 0.5wt% to 4wt%, the obtained battery separator can have excellent heat resistance and conductivity, and also has high wettability, and is then applied to batteries, which can effectively improve the safety and electrical performance of the batteries. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0065] Example 1
[0066] A battery separator, comprising a substrate and a coating layer coated on one side of the substrate;
[0067] Wherein, the substrate is a polyethylene film with a thickness of 7 μm;
[0068] The coating layer has a thickness of 3 μm and includes aluminum oxide particles (D 50 The particle size is 0.5 μm), acrylic adhesive (purchased from Xinyuanbang Technology Co., Ltd., brand AS-231 series), esterified nanocellulose fibers (average diameter is 300 nm) and lithiated nanofiber microspheres (D 50 Particle size is 50 μm);
[0069] The content of ester groups in the coating layer per square meter is 2wt%, and the content of lithium ions is 0.16wt%;
[0070] The total mass of the esterified nanocellulose fibers and the lithiated nanofiber microspheres, the mass ratio of the acrylic adhesive to the alumina particles is 0.2:0.05:1, and the mass ratio of the esterified nanocellulose fibers to the lithiated nanofiber microspheres is 1:0.3;
[0071] The method for preparing the battery separator provided in this embodiment comprises the following steps:
[0072] 20 parts by weight of aluminum oxide particles and 1 part by weight of citric acid were mixed in water, and stirred at 1800 rpm and 30° C. for 1.5 hours to obtain a premixed solution of aluminum oxide particles with a content of 20 wt%;
[0073] 100 parts by weight of nanofiber microspheres are added to 1000 parts by weight of a 20 wt% lithium hydroxide solution for lithiation treatment at room temperature for 7 hours, and then washed with deionized water and freeze-dried to obtain lithiated nanofiber microspheres;
[0074] 68 parts by weight of cellulose fibers and 1 part by weight of citric acid were mixed in water to obtain a 4 wt% cellulose fiber premix, and the obtained cellulose fiber premix was placed in an ultrasonic cavitation machine at a frequency of 30 kHz and 1 m 3 / hr, and after 30 minutes of treatment, an esterified cellulose fiber premix is obtained, which is washed with deionized water, filtered and dried to obtain esterified microcrystalline cellulose fibers; 150 parts by weight of the obtained esterified microcrystalline cellulose fibers are added to 30 mL of dimethylacetamide, stirred for 1 hour, and then 300 mL of a 40% tetrabutylammonium hydroxide aqueous solution is added to react for 5 hours, and then excess methanol is added until no precipitation is produced, and then the mixture is washed alternately with methanol and water for 6 times, and a filter cake is obtained after washing and filtering, and the obtained filter cake is dialyzed to obtain a suspension, and the obtained suspension is dried to obtain esterified nanocellulose fibers;
[0075] 80 parts by weight of a 20 wt% alumina particle premix, 3.2 parts by weight of esterified nanocellulose fibers and 0.96 parts by weight of lithiated nanofiber microspheres were subjected to cavitation treatment in 16 parts by weight of water, the cavitation treatment time was 0.5 h, the temperature was 40° C., the power was 25 kHz, and then 0.8 parts by weight of an acrylic adhesive was added for dispersion to obtain a slurry with a viscosity of 20 cp;
[0076] The obtained slurry is coated on one surface of a polyethylene-based film and dried to obtain the battery separator.
[0077] Example 2
[0078] A battery separator, comprising a substrate and a coating layer coated on one side of the substrate;
[0079] Wherein, the substrate is a polyethylene film with a thickness of 7 μm;
[0080] The coating layer has a thickness of 1.8 μm and includes aluminum oxide particles (D 50 The particle size is 0.2 μm), acrylic adhesive (purchased from Xinyuanbang Technology Co., Ltd., brand AS-231 series), esterified nanocellulose fibers (average diameter is 150 nm) and lithiated nanofiber microspheres (D 50 Particle size is 20 μm);
[0081] The content of ester groups in the coating layer per square meter is 1wt%, and the content of lithium ions is 0.1wt%;
[0082] The total mass of the esterified nanocellulose fibers and the lithiated nanofiber microspheres, the mass ratio of the acrylic adhesive to the alumina particles is 0.05:0.04:1, and the mass ratio of the esterified nanocellulose fibers to the lithiated nanofiber microspheres is 1:0.3;
[0083] The method for preparing the battery separator provided in this embodiment comprises the following steps:
[0084] 18 parts by weight of aluminum oxide particles and 1 part by weight of citric acid were mixed in water, and stirred at 2000 rpm and 20° C. for 2 hours to obtain a premixed solution of aluminum oxide particles with a content of 20 wt %;
[0085] 100 parts by weight of nanofiber microspheres are added to 1000 parts by weight of 20% lithium hydroxide solution for lithiation treatment at room temperature for 8 hours, and then washed with deionized water and freeze-dried to obtain lithiated nanofiber microspheres;
[0086] 34 parts by weight of cellulose fibers and 1 part by weight of citric acid are mixed in water to obtain a cellulose fiber premix with a concentration of 4wt%, the obtained cellulose fiber premix is placed in an ultrasonic cavitation machine, and circulated at a frequency of 40kHZ and a flow rate of 0.5m3 / hr. After 30 minutes of treatment, an esterified cellulose fiber premix is obtained, which is washed with deionized water, filtered and dried to obtain esterified microcrystalline cellulose fibers; 150 parts by weight of the obtained esterified microcrystalline cellulose fibers are added to 30mL of a dimethylacetamide solvent with a concentration of , stirred for 1h, and then 300mL of a 40% tetrabutylammonium hydroxide aqueous solution is added to react for 5h, and then excess methanol is added until no precipitation is produced, and then the solution is washed alternately with methanol and water for 5 times, and the filter cake obtained after washing and filtration is dialyzed to obtain a suspension, and the obtained suspension is dried to obtain esterified nanocellulose fibers;
[0087] 80 parts by weight of a 20 wt% alumina particle premix, 0.8 parts by weight of esterified nanocellulose fibers and 0.24 parts by weight of lithiated nanofiber microspheres were subjected to cavitation treatment in 6.4 parts by weight of water, the cavitation treatment time was 0.5 h, the temperature was 60° C., the power was 20 kHz, and then 0.64 parts by weight of an acrylic adhesive was added for dispersion to obtain a slurry with a viscosity of 10 cp;
[0088] The obtained slurry is coated on one surface of a polyethylene-based film and dried to obtain the battery separator.
[0089] Example 3
[0090] A battery separator, comprising a substrate and a coating layer coated on one side of the substrate;
[0091] Wherein, the substrate is a polyethylene film with a thickness of 7 μm;
[0092] The coating layer has a thickness of 5 μm and includes aluminum oxide particles (D 50 The particle size is 1 μm), acrylic adhesive (purchased from Xinyuanbang Technology Co., Ltd., brand AS-231 series), esterified nanocellulose fibers (average diameter of 500 nm) and lithiated nanofiber microspheres (D 50 Particle size is 200 μm);
[0093] The content of ester groups in the coating layer per square meter is 3wt%, and the content of lithium ions is 0.22wt%;
[0094] The total mass of the esterified nanocellulose fibers and the lithiated nanofiber microspheres, the mass ratio of the acrylic adhesive to the alumina particles is 0.3:0.06:1, and the mass ratio of the esterified nanocellulose fibers to the lithiated nanofiber microspheres is 1:0.3;
[0095] The method for preparing the battery separator provided in this embodiment comprises the following steps:
[0096] 24 parts by weight of aluminum oxide particles and 1 part by weight of citric acid were mixed in water, and stirred at 1500 rpm and 50° C. for 1 hour to obtain a premixed solution of aluminum oxide particles with a content of 20 wt%;
[0097] 100 parts by weight of nanofiber microspheres are added to 1000 parts by weight of a 20 wt% lithium hydroxide solution for lithiation treatment at room temperature for 5 hours, and then washed with deionized water and freeze-dried to obtain lithiated nanofiber microspheres;
[0098] 51 parts by weight of cellulose fibers and 1 part by weight of citric acid are mixed in water to obtain a cellulose fiber premix with a concentration of 4wt%, and the obtained cellulose fiber premix is placed in an ultrasonic cavitation machine, and circulated at a frequency of 25kHZ and a flow rate of 2m3 / hr. After 30 minutes of treatment, an esterified cellulose fiber premix is obtained, which is washed with deionized water, filtered and dried to obtain esterified microcrystalline cellulose fibers; 150 parts by weight of the obtained esterified microcrystalline cellulose fibers are added to 30mL of dimethylacetamide with a concentration of , stirred for 1h, and then 300mL of 40% tetrabutylammonium hydroxide aqueous solution is added to react for 5h, and then excess methanol is added until no precipitation is produced, and then washed alternately with methanol and water for 6 times, and the filter cake obtained after washing and filtering is dialyzed to obtain a suspension, and the obtained suspension is dried to obtain esterified nanocellulose fibers;
[0099] 80 parts by weight of a 20 wt% alumina particle premix, 4.8 parts by weight of esterified nanocellulose fibers and 1.44 parts by weight of lithiated nanofiber microspheres were cavitated in 30.5 parts by weight of water for 0.5 h at a temperature of 30° C. and a power of 30 kHz, and then 1.33 parts by weight of an acrylic adhesive was added for dispersion to obtain a slurry with a viscosity of 40 cp;
[0100] The obtained slurry is coated on one surface of a polyethylene-based film and dried to obtain the battery separator.
[0101] Example 4
[0102] A battery separator, which differs from Example 1 in that the amount of esterified nanocellulose fibers in the slurry is adjusted to 8.5 parts by weight so that the ester content in the coating layer is 0.5wt%, and other structures, parameters and steps are the same as Example 1.
[0103] Example 5
[0104] A battery separator, which differs from Example 1 in that the amount of esterified nanocellulose fibers in the slurry is adjusted to 68 parts by weight, so that the content of ester groups in the coating layer is 4wt%, and other structures, parameters and steps are all referred to Example 1.
[0105] Example 6
[0106] A battery separator, which differs from Example 1 in that the coating layer does not contain lithiated nanofiber microspheres, and other structures, parameters and steps are the same as those of Example 1.
[0107] Example 7
[0108] A battery separator, which differs from Example 1 in that the total mass of esterified nanocellulose fibers and lithiated nanofiber microspheres, and the mass ratio of acrylic adhesive to alumina particles are 0.1:0.05:1, and other structures, parameters and steps are all referenced to Example 1.
[0109] Example 8
[0110] A battery separator, which differs from Example 1 in that the total mass of esterified nanocellulose fibers and lithiated nanofiber microspheres, and the mass ratio of acrylic adhesive to alumina particles are 0.4:0.05:1, and other structures, parameters and steps are all referenced to Example 1.
[0111] Example 9
[0112] A battery separator, which differs from Example 1 in that the total mass of esterified nanocellulose fibers and lithiated nanofiber microspheres, and the mass ratio of acrylic adhesive to alumina particles are 0.2:0.02:1, and other structures, parameters and steps are all referenced to Example 1.
[0113] Example 10
[0114] A battery separator, which differs from Example 1 in that the total mass of esterified nanocellulose fibers and lithiated nanofiber microspheres, and the mass ratio of acrylic adhesive to alumina particles are 0.2:0.1:1, and other structures, parameters and steps are all referenced to Example 1.
[0115] Embodiment 11
[0116] A battery separator, which differs from Example 1 in that the mass ratio of esterified nanocellulose fibers to lithiated nanofiber microspheres is 1:0.1, and other structures, parameters and steps are the same as those of Example 1.
[0117] Example 12
[0118] A battery separator, which differs from Example 1 in that the mass ratio of esterified nanocellulose fibers to lithiated nanofiber microspheres is 1:0.8, and other structures, parameters and steps are the same as those of Example 1.
[0119] Comparative Example 1
[0120] A battery separator, which differs from Example 1 in that the amount of esterified nanocellulose fibers in the slurry is adjusted to 3.4, so that the content of ester groups in the coating layer is 0.2wt%, and other structures, parameters and steps are all referred to Example 1.
[0121] Comparative Example 2
[0122] A battery separator, which differs from Example 1 in that the amount of esterified nanocellulose fibers in the slurry is adjusted to 85, so that the content of ester groups in the coating layer is 5wt%, and other structures, parameters and steps are all referred to Example 1.
[0123] Comparative Example 3
[0124] A battery separator, which differs from Example 1 in that nanocellulose fibers are used to replace esterified nanocellulose fibers, and other structures, parameters and steps are the same as those of Example 1.
[0125] Performance Testing:
[0126] (1) Wettability of electrolyte: The contact angle measurement method is used to test the contact angle by dropping propylene carbonate electrolyte onto the surface of the battery separator. A contact angle close to 0 degrees indicates good electrolyte wettability, while a contact angle close to 90 degrees indicates poor wettability. For specific testing, please refer to GB / T 30693-2014 standard.
[0127] (2) Heat resistance: 11 A4 papers were clamped on the upper and lower sides of the battery separator. Initial marking lines of 100 mm × 100 mm were pre-marked on the battery separator to be tested along the MD and TD directions of the battery separator. The separator was baked in an oven at 200°C for 1 h. The distance between the marking lines was tested and the shrinkage rate (%) was calculated as (distance between the initial marking lines - distance between the marking lines after baking) / distance between the initial marking lines × 100%.
[0128] (3) Moisture content: The Karl Fischer method (capacitance method) is used to test the moisture content of the battery separator. The moisture content is tested based on the volume of consumed reagents and the titration degree.
[0129] (4) Tensile strength: The test was carried out using a universal tensile testing machine, with specific reference to the GB / T36363-2018 series standard.
[0130] The battery separators provided by Examples 1 to 12 and Comparative Examples 1 to 3 were tested according to the above test method. The test results are shown in Table 1:
[0131] Table 1
[0132]
[0133]
[0134] From the data in Table 1, we can see that:
[0135] The battery separators provided in Examples 1 to 12 have excellent electrolyte wettability, heat resistance and mechanical properties, and also have a suitable moisture content; in particular, the contact angle of the battery separators provided in Examples 1 to 3 is only 14 to 32°, the thermal shrinkage rate in the MD direction is only 1.2 to 2.5%, the thermal shrinkage rate in the TD direction is only 0.9 to 1.6%, the tensile strength in the MD direction is as high as 2430 to 3211 MPa, the tensile strength in the TD direction is as high as 2078 to 2675 MPa, and the moisture content is 1259 to 1803 ppm, combining the best electrolyte wettability, heat resistance and mechanical properties.
[0136] By comparing the data of Example 1, Examples 4 to 5 and Comparative Examples 1 to 2, it can be seen that if the content of ester groups contained in the coating layer per square meter in the battery separator becomes lower, the electrolyte wettability of the battery separator will decrease, and the heat resistance will also deteriorate; and if the content of ester groups contained in the coating layer per square meter in the battery separator becomes higher, it will lead to excessive moisture content in the battery separator and excessive polar groups in the coating layer, which will easily lead to a potential difference at the positive and negative electrode ends of the battery, resulting in a series of problems such as failure and bulging.
[0137] Comparing the data of Example 1 and Comparative Example 3, it can be seen that the use of nanocellulose fibers to replace esterified nanocellulose fibers will lead to a decrease in the electrolyte wettability, heat resistance and tensile strength of the resulting battery separator, and will also lead to a significant increase in the moisture content.
[0138] Further comparison of the data of Example 1 and Example 6 shows that if the coating layer does not contain lithiated nanofiber microspheres, the tensile strength of the resulting battery separator will decrease.
[0139] Finally, by comparing the data of Example 1 and Examples 7 to 12, it can be seen that if the mass ratio of the esterified nanocellulose fibers, the lithiated nanofiber microsphere acrylate adhesive and the aluminum oxide particles in the coating layer is not within the range defined by the present invention, the resulting battery separator will not have the best electrolyte wettability, heat resistance and mechanical properties.
[0140] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A battery separator, characterized in that: The battery separator comprises a substrate and a coating layer disposed on one or both sides of the substrate; The coating layer comprises inorganic particles, acrylic adhesive and esterified nanocellulose fibers; The content of ester groups in the coating layer is 0.5 wt % to 4 wt % per square meter.
2. The battery separator according to claim 1, characterized in that: The content of ester groups in the coating layer is 1 wt% to 3 wt% per square meter. Preferably, the coating layer has a thickness of 0.5 μm to 5 μm.
3. The battery separator according to claim 1 or 2, characterized in that: The average diameter of the esterified nanocellulose fibers is 100 nm to 500 nm; Preferably, the inorganic particles have a D 50 Particle size is 0.1μm~1μm; Preferably, the inorganic particles include any one of boehmite, alumina or silica, or a combination of at least two of them.
4. The battery separator according to any one of claims 1 to 3, characterized in that: The coating layer also includes lithiated nanofiber microspheres; Preferably, the inorganic particles have a D 50 Particle size and D of lithiated nanofiber microspheres 50 The ratio of particle size is 1:(2-200); Preferably, the content of lithium ions in the coating layer per square meter is 5% to 15% of the ester group content, and more preferably 7% to 10%.
5. The battery separator according to any one of claims 4, characterized in that: The mass ratio of the total mass of the esterified nanocellulose fibers and the lithiated nanofiber microspheres to the inorganic particles is (0.1-0.4):1, preferably (0.05-0.3):1; Preferably, the mass ratio of the acrylic adhesive to the inorganic particles is (0.02-1):1, more preferably (0.03-0.06):
1. Preferably, the mass ratio of the esterified nanocellulose fibers to the lithiated nanofiber microspheres is 1:(0.1-0.5), and more preferably 1:(0.2-0.3).
6. A method for preparing a battery separator, characterized in that: The preparation method comprises: coating the slurry on one side or both sides of the substrate, and drying to obtain the battery separator; The slurry is obtained by uniformly mixing inorganic particles, acrylic adhesive, esterified nanocellulose fibers and optionally lithiated nanofiber microspheres in water.
7. The preparation method according to claim 6, characterized in that: The viscosity of the slurry is 10cp to 100cp; Preferably, the content of inorganic particles in the slurry is 15wt% to 25wt%; Preferably, the content of the acrylic adhesive in the slurry is 0.1wt% to 1wt%; Preferably, the content of esterified nanocellulose fibers in the slurry is 1 wt% to 5 wt%; Preferably, the content of the lithiated nanofiber microspheres in the slurry is 0.5wt% to 1.5wt%.
8. The preparation method according to claim 7, characterized in that: The preparation method of the slurry comprises the following steps: Mixing inorganic particles and carboxylic acid dispersant A in water to obtain an inorganic particle premix solution; The nanofiber microspheres are subjected to a lithiation treatment to obtain lithiated nanofiber microspheres; The cellulose fibers and the carboxylic acid dispersant B are mixed in water to obtain a cellulose fiber premix, the obtained cellulose fiber premix is placed in an ultrasonic cavitation machine for circulation treatment, filtered and dried to obtain esterified microcrystalline cellulose fibers, the obtained esterified microcrystalline cellulose fibers are added to dimethylacetamide for stirring, and then tetrabutylammonium hydroxide is added for reaction, washed and filtered to obtain a filter cake, the obtained filter cake is dialyzed to obtain a suspension, and the obtained suspension is dried to obtain esterified nanocellulose fibers; The inorganic particle premix, esterified nanocellulose fibers and lithiated nanofiber microspheres are dispersed in water, placed in an ultrasonic cavitation machine for cavitation treatment, and an acrylic ester adhesive is added for dispersion to obtain the slurry.
9. The preparation method according to claim 8, characterized in that: The carboxylic acid dispersant A and the carboxylic acid dispersant B each independently include any one of citric acid, malic acid, tartaric acid or oxalic acid or a combination of at least two thereof; Preferably, the mass ratio of the carboxylic acid dispersant A to the inorganic particles is 1:(16-24); Preferably, the mass ratio of the carboxylic acid dispersant B to the cellulose fiber is (0.1-1):(10-50); Preferably, the method of placing the obtained cellulose fiber premix in an ultrasonic cavitation machine for circulation treatment comprises: placing the cellulose fiber premix in an ultrasonic cavitation machine at a frequency of 20 kHz to 40 kHz and a frequency of 0.2 m 3 / hr~2m 3 / hr flow rate for 20min~40min; Preferably, the temperature for cavitation treatment in the ultrasonic cavitation machine is 25° C. to 60° C., the time is 0.3 h to 0.8 h, and the frequency is 20 kHz to 30 kHz.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises at least one of the battery separators according to any one of claims 1 to 5, or the battery separators prepared by the preparation method according to any one of claims 6 to 9.